Interferon-γ inhibits gastric carcinogenesis by inducing epithelial cell autophagy and T cell apoptosis - Tu, Shui Ping (2011)
Interferon-gamma (IFN-γ) mediates responses to bacterial infection and autoimmune disease but it is also an important tumor suppressor. IFN-γ is upregulated in the gastric mucosa by chronic Helicobacter infection; however, whether it plays a positive or negative role in inflammation-associated gastric carcinogenesis is unexplored. To study this question we generated an H+/K+-ATPase-IFN-γ transgenic mouse that overexpresses murine IFN-γ in the stomach mucosa. In contrast to the expected pro-inflammatory role during infection, we found that IFN-γ overexpression failed to induce gastritis and instead inhibited gastric carcinogenesis induced by IL-1beta (IL-1β) and/or Helicobacter infection. Th1 and Th17 immune responses were inhibited by IFN-γ through Fas induction and apoptosis in CD4 T cells. IFN-γ also induced autophagy in gastric epithelial cells through increased expression of Beclin-1. Lastly, in the gastric epithelium, IFN-γ also inhibited IL-1β- and Helicobacter-induced epithelial apoptosis, proliferation, and Dckl1+ cell expansion. Taken together, our results suggest that IFN-γ coordinately inhibits bacterial infection and carcinogenesis in the gastric mucosa by suppressing putative gastric progenitor cell expansion and reducing epithelial cell apoptosis via induction of an autophagic program.